Recognising patterns of authentic inquiry-based approach to foster children’s scientific reasoning process - Bembich, Caterina; Bologna, Valentina (Frontiers in Education, 2025)
The objectives of the ONU Agenda 2030 and the actions outlined in 2020 in the European agenda for skills underline the importance of bringing students closer to STEM (Science, Technology, Engineering and Mathematics) subjects and consequently promote scientific education to accompany schools in the ecological and cultural transition. The global and European recognition of the importance of developing learning paths that immediately introduce children to scientific disciplines raises the need to think about learning environments and teaching paths that effectively promote the development of scientific thinking. The approach to STEM disciplines should be interdisciplinary and develop disciplinary and transversal skills, such as creativity, critical thinking, reasoning, and social, economic and environmental skills. The Investigative Science Learning Environment (ISLE) is an example of an authentic inquiry approach, which promotes and fosters students’ scientific abilities with active learning settings and activities. In this study, we focus on an example of how to develop children’s scientific thinking using the ISLE approach. From a cognitive and non-cognitive point of view, we recognise the main features of the activated process in the learning sequences and identify patterns in their physical “babbling” reasoning, which is sustained by the teacher’s scaffolding.